A class of nonparametric bivariate survival function estimators for randomly censored and truncated data. Issue 4 (1st October 2016) - Dai, Hongsheng; Restaino, Marialuisa; Wang, Huan
ABSTRACT: This paper proposes a class of nonparametric estimators for the bivariate survival function estimation under both random truncation and random censoring. In practice, the pair of random variables under consideration may have certain parametric relationship. The proposed class of nonparametric estimators uses such parametric information via a data transformation approach and thus provides more accurate estimates than existing methods without using such information. The large sample properties of the new class of estimators and a general guidance of how to find a good data transformation are given. The proposed method is also justified via a simulation study and an application on an economic data set.